MicroRNAs (20a, 146a, 155, and 145) expressions in a sample of Iraqi patients with multiple sclerosis - Aljawadi, Zainab A.; Al-Derzi, Aida R.; Abdul-Majeed, Ban A.; Almahdawi, Akram M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Multiple sclerosis is a devastating central nervous system autoimmune disorder that is characterized by a series of inflammations, demyelinations, and neurodegenerations that affect the brain and spinal cord. The epigenetic studies specially micro Ribonucleic acid expression represent an important field of researches that probably uncover the obscurities behind the multiple sclerosis pathogenesis. Objectives: to study the expression of micro Ribonucleic acids (20a, 146a, 155, and 145) in multiple sclerosis patients by the use of real time polymerase chain reaction. Patients and Methods: A case-control study was performed using real time polymerase chain reaction technique to measure the relative expression of micro Ribonucleic acids (20a, 146a, 155, and 145) in peripheral blood leukocytes of 25 newly diagnosed untreated multiple sclerosis patients and comparing them with that of 25 clinically apparent healthy controls . Results: Studying of micro Ribonucleic acids expression in multiple sclerosis patients revealed a significant down-regulation in micro Ribonucleic acid-20a while up- regulation of micro Ribonucleic acid-155 expression in multiple sclerosis patients in comparison to controls. Micro Ribonucleic acids -146a and 145 were not associated with significant changes in its expression in multiple sclerosis patients in comparison to controls. Conclusion: multiple sclerosis is associated with significant changes in micro Ribonucleic acids expression including micro Ribonucleic acid-20a, and micro Ribonucleic acid-155 but not micro Ribonucleic acid 146a and-145 that can be measured by real time polymerase chain reaction technique.